The sexuality of people with disabilities in the critical intercultural perspective in the school context (Research, Society and Development, 2022)
This study deals with the sexuality of people with disabilities in the critical intercultural perspective in the school context, with the objective of verifying how sexuality can be worked at school. The study is characterized by being a qualitative research and the methodological procedure carried out was outlined through a bibliographic survey. Among the theoretical framework of the research, Candau (2016), Denari (2006), Fleuri (2003), Louro (2008), Oliveira (2015), Maia and Aranha (2005), Maia (2001), Maia; Ribeiro (2010, 2011), Sacavino (2016), among others. The results showed that teachers have many difficulties in working on the topic of sexuality in an intercultural perspective and, above all, of people with disabilities, since different aspects favor the homogeneity, standardization and monoculturality of disabled bodies. It was also found that society continues with prejudiced thinking about the sexuality of people with disabilities, who are seen as sexually deprived of their sexual desires, impulses and manifestations, or that their expressed sexual behaviors do not correspond to their disability condition, for that do not behave in a way corresponding to their sexual characteristics.